Digital surveillance in a pandemic response: What bioethics ought to learn from Indigenous perspectives. (18th February 2022) - Hendl, Tereza; Roxanne, Tiara
Abstract: Our paper interrogates the ethics of digital pandemic surveillance from Indigenous perspectives. The COVID‐19 pandemic has shown that Indigenous peoples are among the communities most negatively affected by pandemic infectious disease spread. Similarly to other racialized subpopulations, Indigenous people have faced strikingly high mortality rates from COVID‐19 owing to structural marginalization and related comorbidities, and these high rates have been exacerbated by past and present colonial dominance. At the same time, digital pandemic surveillance technologies, which have been promoted as effective tools for mitigating a pandemic, carry risks for Indigenous subpopulations that warrant an urgent and thorough investigation. Building on decolonial scholarship and debates about Indigenous data sovereignty, we argue that should Indigenous communities wish to implement digital pandemic surveillance, then they must have ownership over these technologies, including agency over their own health data, how data are collected and stored, and who will have access to the data. Ideally, these tools should be designed by Indigenous peoples themselves to ensure compatibility with Indigenous cultures, ethics and languages and the protection of Indigenous lives, health and wellbeing.